2020
DOI: 10.1080/22797254.2020.1816142
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of forest canopy fuel parameters in managed boreal forests using multispectral and unispectral airborne laser scanning data and aerial images

Abstract: This study evaluated the suitability of different airborne laser scanning (ALS) datasets for the prediction of forest canopy fuel parameters in managed boreal forests in Finland. The ALS data alternatives were leaf-off and leaf-on unispectral and leaf-on multispectral data, alone and combined with aerial images. Canopy fuel weight, canopy base height, biomass of living and dead trees, and height and biomass of the understory tree layer were predicted using regression analysis. The considered categorical forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Intensity measures were derived from the raw discrete-return LiDAR data (provided separately), but we did not have access to the proprietary software employed for correcting atmospheric and noise effects; thus, we could not regenerate the single-channel point clouds. Therefore, the contribution of each channel to the final models cannot be proved experimentally at the present time in our case, but there is at least a strong evidence from the results of Reference [73] mentioned in Section 1. Nevertheless, the existence of a second channel effectively doubles the point cloud density (reaching to an average of 82.99 points/m 2 ), which is highly expected to increase the surface fuel estimation potential, even if that cannot be proven experimentally.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Intensity measures were derived from the raw discrete-return LiDAR data (provided separately), but we did not have access to the proprietary software employed for correcting atmospheric and noise effects; thus, we could not regenerate the single-channel point clouds. Therefore, the contribution of each channel to the final models cannot be proved experimentally at the present time in our case, but there is at least a strong evidence from the results of Reference [73] mentioned in Section 1. Nevertheless, the existence of a second channel effectively doubles the point cloud density (reaching to an average of 82.99 points/m 2 ), which is highly expected to increase the surface fuel estimation potential, even if that cannot be proven experimentally.…”
Section: Discussionmentioning
confidence: 65%
“…The results suggested that multispectral intensity information is useful in the examination of forest understory. The estimation of canopy fuel parameters was addressed in Reference [73], where a comparative analysis of unispectral and multispectral LiDAR data was performed for the prediction of canopy fuel weight, canopy base height, vegetation height and biomass through regression analysis. The results of this research highlighted the usefulness of multispectral LiDAR compared to the unispectral LiDAR data in the examination of forest fuel parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings revealed that although the incorporation of intensity metrics yielded a modest enhancement in accuracy, the significance of these metrics becomes particularly pronounced when dealing with lower-resolution data in the context of 1 m and 2 m voxel models. The results of Maltamo et al [ 113 ] substantiated the better efficiency of MSL in the prediction of forest canopy fuel parameters, including canopy fuel weight, canopy base height, biomass of living and dead trees, and height and biomass of the understory tree layer and site fertility. In 2023, Rana et al [ 114 ] showed that MSL is superior to the combination of traditional monochromatic LiDAR and color–infrared image in monitoring seedling stands.…”
Section: Multispectral Lidar Applicationsmentioning
confidence: 93%
“…In fact, multispectral LiDAR systems have the ability to provide information on the vertical distribution of physiological processes in different spectral channels [64]. In recent years, the multispectral LiDAR point clouds have been widely used for land cover classification [65], tree species composition [66], surface [37] and forest canopy fuel load estimation [67]. Additionally, the multispectral LiDAR data provided more accurate AGB estimations [68] and individual tree detection compared with the monospectral [69].…”
Section: Introductionmentioning
confidence: 99%